The Power of the Voice: From Voice-Over to Character? - Rim KHALED (E-REA)
The use of voice-over narration was frowned upon over the course of the 20th century, and it is only after the 1980s that it was accepted and became more prevalent in the film and television industry (Kozloff 12-13). The following decade was marked by more experimentation with this narrative technique leading to the creation of diverse narrator profiles. This is illustrated in a miscellany of TV series, such as Desperate Housewives and Jane the Virgin, wherein the voice-over narrator plays an important narratological function. As these two series showcase, voice-over narrators can be either homodiegetic or heterodiegetic. Accordingly, the former exists in the storyworld as a character, while the latter does not. This paper hypothesizes that under certain circumstances, heterodiegetic voice-over narrators can become characters despite their incorporeality on the screen, thanks to the power of the voice.